1968
DOI: 10.2307/4593308
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Sorbing Substances in the FTA-ABS Test for Syphilis: A Preliminary Study

Abstract: are research microbiologists and Mr. Skaggs is a biological laboratory technician (microbiology), Treponematoses Group,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…It seemed probable that it owed its activity to heatstable material from the treponemes which reacted with the group antibody. The demonstration by Cannefax, Hanson, and Skaggs (1968) that a sorbate prepared from an uninoculated culture appeared to be as effective as that made from medium in which Reiter treponemes had been grown has been confirmed in the present study. These authors also found sorbing activity present in the yeast extract present in their medium and in Bacto casitone.…”
Section: Discussionsupporting
confidence: 80%
“…It seemed probable that it owed its activity to heatstable material from the treponemes which reacted with the group antibody. The demonstration by Cannefax, Hanson, and Skaggs (1968) that a sorbate prepared from an uninoculated culture appeared to be as effective as that made from medium in which Reiter treponemes had been grown has been confirmed in the present study. These authors also found sorbing activity present in the yeast extract present in their medium and in Bacto casitone.…”
Section: Discussionsupporting
confidence: 80%
“…Expensive equipment and skilled staff are necessary for the execution of the TPI and FTA-ABS tests and for the interpretation of results. Criticisms have been made of the immunological specificity of the sorbent used in the FTA-ABS test by several workers (Cannefax, Hanson, and Skaggs, 1968;Rathlev, 1968;Wilkinson and Ferguson, 1968), and of its failure to remove all group reactive antibody from some sera (Kiraly, Jobbagy, and Kovats, 1967;Wilkinson and Wiseman, 1971). False positive FTA-ABS tests have also been reported (Fife, 1964;Buchanan and Haserick, 1970;Kraus, Haserick, and Lantz, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has since been shown that the sorbent used is not specific and that medium on which the Reiter treponeme is grown (Wilkinson and Ferguson, 1968), a digest of casein which is present in such a medium (Cannefax et al , 1968) and even other substances such as yeasts, VDRL antigen or extracts of gonococci (Rathlev, 1968) would serve instead, indicating that some nonspecific physicochemical factor is responsible for its action.…”
Section: Diagnosis Of Syphilismentioning
confidence: 99%